Treatment pathway for sacral neuromodulation in faecal incontinence: An update Behandlungspfad für die sakrale Neuromodulation bei Stuhlinkontinenz: Ein Update - Kahlke, Volker; Fürst, Alois; Schwandner, Oliver; Matzel, Klaus (Coloproctology, 2023)
Sacral nerve modulation (SNM) has become an important tool in the therapy of fecal incontinence over the years, and is now the core treatment after failure of conservative therapy. Due to the successful implementation of this method in Germany and some changes in the surgical procedure, an update of the in 2014 published treatment pathway was necessary. As the original, this update serves as a recommendation of the authors for the treatment of fecal incontinence with SNM.
CRIS-Team Scopus Importer:2023-12-29
Keywords: Biofeedback; Cochrane Collaboration; Fecal incontinence; Sacral nerve modulation; Sacral nerve stimulation